Investigation of mechanical properties and heat transfer of welded joint of AA6061 and AA7075 using TIG+FSP welding approach - Mehdi, Husain; Mishra, R.S. (Journal of advanced joining processes, 2020)
Joining of dissimilar aluminum alloys are required in many engineering applications. The fusion welding often results in defective weld like porosity, micro cracks, coarse grain structure and high residual stress. To avoid these defects the top surface of Tungsten inert gas (TIG) welded joint are processed using friction stir processing (FSP). In this work, The influences of friction stir processing on the TIG welding with filler wire ER4043 and ER5356 for dissimilar aluminum alloy AA6061 and AA7075 were carried out and investigate the residual stresses and mechanical properties of (TIG+FSP) welded joint and analyze the finite element formulation and mathematical equations of heat transfer and material flow of TIG + FSP welded joint using ANSYS fluent software by adjusting the processing parameters of FSP. The results show that the maximum compressive residual stress 64 MPa were obtained at the fusion zone (FZ) of the TIG weldment with filler ER4043, whereas minimum compressive residual stress 39 MPa was obtained at stir zone (SZ) of the TIG+FSP with filler 5356. The maximum heat flux 5.33 × 106 W/m2 and temperature 511 °C were observed at tool rotation 1300 rpm with feed rate 44 mm/min. These results give the satisfactory measure of confidence in the fidelity of simulation.